Development of a Qualitative Assessment Instrument for Cognitive Processes in Gaming Decision - Diantina, Fanni Putri; Permana, Rizka Hadian; Khasanah, Andhita Nurul; Pratama, Rifky Abdila; Halwa, Aqyla; Rahma, Dianita; Poerwandari, Elizabeth Kristi; Indirasari, Dyah Triarini (Universitas Islam Bandung, 2023)
Indonesia ranks 6th with the highest number of online gamers in Asia and 12th in the world gaming market. When online gamers become addicted, they lose the ability to halt or control their gaming behavior, leading to problematic behavior. Decision-making processes at the cognitive level are considered relevant in various addictive behaviors, including inappropriate gaming behavior. Exploratory research can be conducted using a qualitative technique, with data collected through in-depth interviews, to acquire an in-depth understanding of the comparison of the interaction process of each cognitive component in decision-making to play online games. This research was conducted in Bandung from December 2021 to December 2022. Steps are needed to develop guidelines that explore the functioning of affective and cognitive responses (coping, cognitive and affective bias, and craving and urge) and executive and inhibitory control. The guideline used a cognitive theoretical framework in addictive behavior, namely the I-PACE model, with a multidimensional theoretical basis. Through theoretical deepening, it was derived as a guideline divided into three main aspects, four sub-aspects, 32 main questions, and 36 probing questions.